Can Prospect Theory Explain the Disposition Effect? A New Perspective on Reference Points - Meng, Juanjuan; Weng, Xi (Management Science, 2018)
There has been recent debate about whether prospect theory can explain the disposition effect. Using both theory and simulation, this paper shows that prospect theory often predicts the disposition effect when lagged expected final wealth is the reference point under the principle of preferred personal equilibrium, regardless of whether the reference point is updated or not. When initial wealth is the reference point, however, there is often no disposition effect. Models that use a reference point with no lag under the principle of preferred personal equilibrium or that determine the reference point using the principle of disappointment aversion cannot explain why the investor bought a stock in the first place. Reference point adjustment weakens the disposition effect, leads to more aggressive initial stock purchase strategies, and predicts history dependence in stock holding. This paper was accepted by John List, behavioral economics.